Neighborhood Resources and Social Participation Among Older Adults: Results From the VoisiNuage Study. (March 2013) - Richard, Lucie; Gauvin, Lise; Kestens, Yan; Shatenstein, Bryna; Payette, Hélène; Daniel, Mark; Moore, Spencer; Levasseur, Mélanie; Mercille, Geneviève
Objective: This article examined the associations between proximity to selected locations considered to be conducive to social participation, and social participation itself, in urban-dwelling seniors.Methods: A sample of 520 older adults residing in the Montreal area provided reports of social participation and information about health, sociodemographic characteristics, social networks, and perceptions about features of their residential environment. Information about the distance between their home and five locations deemed to be conducive to social participation were obtained from a geographic information system.Results: Analyses showed a significant association between proximity to selected locations and social participation while accounting for individual characteristics and perceptions of neighborhood features (β = 0.37; SE = 0.17; p < 0.05).Discussion: Findings were consistent with contributions highlighting the impact of the built environment on seniors' health-related behavior. Future work would benefit from the use of longitudinal designs and examinations of social participation through alternate channels.